La repercusión de la condición humana en América Latina según Roig - Iriarte Aguilar, Lucía Fernanda (2023)
In Arturo Roig’s writings, reflection on the human condition is closely intertwined with his concern for Latin America. This article explores this connection and proposes the following interpretation: If directing our attention to Our America reveals fundamental aspects of the human condition that are intrinsically related to domination. In summary, this article will address the relationship that Arturo Roig examines between the human condition and the fight against domination in Latin America, highlighting that the human subject finds its most genuine expression in the resistance against forms of oppression, personified by symbols of Caliban and Antigone.